Association between hypothyroidism and metabolic syndrome in Qinghai, China - Fan, Xiaoxia; Yao, Yongli; Chai, Shengjun; Wang, Beibei; Xie, Yanling; Jiang, Yanping; Lin, Lijun; Li, Yanan; Fan, Peiyun; Luo, Wei; Wang, Shuqiong; Song, Kang; et al. (Frontiers in Endocrinology, 2024)
Objective To investigate the epidemiological characteristics of hypothyroidism in Qinghai Province, analyze its related influencing factors, establish the normal reference range of thyroid function, and explore the relationship between thyroid hormone (THs), thyroid stimulating hormone (TSH) and metabolic syndrome (MS) in Qinghai population within the normal range, so as to provide some scientific basis for the prevention and treatment of hypothyroidism in Qinghai Province. Methods A total of 2790 residents aged 18 and over from Qinghai were selected through stratified cluster random sampling. Data were collected via questionnaires, physical examinations, and laboratory tests. Results 1. A total of 2628 eligible residents in Qinghai were included in this study, and the total prevalence of hypothyroidism was 30.25%, among which the prevalence of subclinical hypothyroidism was 29.22%, and the prevalence of clinical hypothyroidism was 1.03%. 2. The prevalence of hypothyroidism in women was significantly higher than that in men (36.69% vs 24.30%); smoking and drinking were risk factors for hypothyroidism. 3. In the excluded subjects, 1544 were abnormal thyroid ultrasound, abnormal thyroid function and/or positive thyroid autoantibodies, and the remaining 1084 were reference populations. According to the reference population data, the 95% reference ranges of TSH, FT4, FT3 were 0.43-5.51 mIU/L, 11.0-20.4 pmol/L, 3.63-5.73 pmol/L, respectively. 4. In the normal thyroid function population in Qinghai, MS and its related components were positively correlated with FT3 and FT4 levels, but not significantly correlated with TSH levels. Conclusion 1. The prevalence of hypothyroidism in adults in Qinghai is relatively high, accounting for about one-thirtieth of the total population. Smoking and drinking have a certain impact on the incidence of hypothyroidism. 2. It provides a reference range for the diagnosis of thyroid diseases in Qinghai province, which is different from that of reagent suppliers, and has certain promotion significance in the western region. 3. MS and its related components are positively correlated with FT3 and FT4 levels, but not with TSH levels in people with normal thyroid function in Qinghai. Early thyroid function screening is of great significance for the prevention of MS.